2012
DOI: 10.1016/j.ijgo.2012.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic prophylaxis for selected gynecologic surgeries

Abstract: Antibiotic prophylaxis may be beneficial in first-trimester suction curettage and laparotomy. No advantage was found for loop electrosurgical excision, hysteroscopy, or laparoscopic gynecologic surgery. Newer procedures and vaginal surgery lack research and merit study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…ciprofloxacin) can be used. Laparoscopic operations not contaminated by the genitourinary or digestive tracts do not require antimicrobial prophylaxis [58].…”
Section: Antimicrobial Prophylaxis and Skin Preparationmentioning
confidence: 99%
“…ciprofloxacin) can be used. Laparoscopic operations not contaminated by the genitourinary or digestive tracts do not require antimicrobial prophylaxis [58].…”
Section: Antimicrobial Prophylaxis and Skin Preparationmentioning
confidence: 99%
“…[18] Moreover, 3 systematic reviews summarizing relative antibiotic prophylaxis for gynecologic procedures without quantitative analysis failed to provide clinical options and failed to reach consistent conclusions. [1921] Therefore, the current study was the first quantitative meta-analysis in this field, and we demonstrated that antibiotic prophylaxis is not necessary for hysteroscopic procedures. And all included trails were performed in the last decade which made the raw data meet the needs of today.…”
Section: Discussionmentioning
confidence: 65%
“…Our interest is on hysteroscopy. To answer this question, Morrill et al [15] refer in their review to Bhattacharya et al [14]. No other new articles on prophylactic antibiotics in hysteroscopy were included.…”
Section: Resultsmentioning
confidence: 99%